INDICATORS OF ARTISTIC CREATIVE GROWTH AND DEVELOPMENT OF AESTHETIC SENSE OF CHILDREN - Raxmatova Ikbolxon Inomjonovna; Cho’tboyeva Mohinabonu Abduhamidovna (Journal of new century innovations, 2022)
Annotation: In this article, the development of aesthetic sense in children, the use of psychological elements in teaching drawing, the issues of developing thinking, distinguishing the size, color, shape, and location of each object in space, the issues related to the deeper perception of the color, rhythm, and proportion of objects in the development of aesthetic sense. , and the indicators of children's artistic and creative growth, children's thinking operations (analysis, synthesis, comparison and generalization) are covered.